Harvesting Optimization, Biomass, and Lipid Content Analysis of Euglena sp. Culture with Ettlia texensis Bioflocculant and Commercial Chitosan - Agus Suyono, Eko; Mudrikah, Siti; Karilanata, Khalid Erlangga; Kurnianto, Dedy; Budiman, Arief; Dewayanto , Nugroho; Putri, Renata Adaranyssa Egistha; Sadewo , Brilian Ryan; Erfianti, Tia (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Bioflocculation technique can improve the harvesting effectiveness of semimass culture of Euglena sp. The addition of E. texensis can significantly increase the flocculation efficiency of Euglena sp. The addition of commercial chitosan was able to increase the flocculation efficiency of Euglena sp. The biomass and lipid content produced by Euglena sp. with E. texensis flocculant agent showed higher results than the biomass and lipid content produced by Euglena sp. with commercial chitosan flocculant agent. Abstract Euglena sp. has a high potential to be developed as biofuel. However, the high cost and energy required for the harvesting process are hindering the production. Flocculation using natural substances, such as microorganisms and biopolymers, offers a promising solution to minimize energy and production costs, so it is applicable on a mass scale. Ettlia texensis is one of the autoflocculating microalgae that can excrete extracellular polymeric substances (EPS). Chitosan is a linear copolymer of D-glucosamine and N-acetyl-D-glucosamine produced by the deacetylation of chitin, which is usually exploited by marine crustaceans, shrimp, and crabs. Chitosan has a very high cation load, so it is often used for coagulation or flocculation. This study explores the potential of E. texensis and chitosan as flocculant agents to harvest the mass culture of Euglena sp. by giving different doses E. texensis with 1:0.25 (E3), 1:0.5 (E4), 1:1 (E5), and 1:2 (E6), and chitosan with 1.25 mg (C1), 2.5 mg (C2), 3.75 mg (C3), and 5 mg (C4). This research began with the cultivation of Euglena sp. and E. texensis on a 50 L scale for 12 days. The effectiveness of flocculation was measured by the spectrophotometric method. Based on this research, the best treatment for harvesting Euglena sp. culture by bioflocculation was shown by the addition of chitosan (5 mg) with the recovery of 84.83%, 0.2213 mg/mL biomass, and 0.2117 mg/mL lipid content. Meanwhile, with E. texensis, the best was shown by the ratio of 1:2 with recovery 84.71%, 0.2053 mg/mL biomass, and 0.1753 mg/mL